The Interplay between Online Learning and Students’ Learning Motivation: A Mixed Method Study - Bachtiar, Bachtiar (Universitas Pahlawan Tuanku Tambusai, 2022)
The Covid -19 Pandemic obligates the education activities to change from face-to-face to fully online activities as the safest and the best options to stop the spread of the virus. Due to the suddent shift from traditional classrooms activities to totally online learning activities, some researches pointed out that students’ motivation for online learning is influenced either intrinsically or extrinsically. This study aims to find out students’ views of online learning and how their learning motivation affects their involvement in English online learning. A Mixed Method Research (MMR) was conducted, employing questionnaire (n=60) and semi-structured interviews (n=6) as the research tools. The quantitative data from the questionnaire were analysed using Statistical Package for Social Sciences (SPSS), while the qualitative data from the interview were analysed employing thematic analysis. The results showed that students overall felt online learning created some obstacles due to unstable internet access and the students didn't interact with their teachers or peers enough. The study also found some advantages of online learning for students, such as more meaningful learning experiences using digital platforms and the opportunity to gain technological knowledge and skills. The study suggests the need for teachers to provide sufficient feedback to students in relation to their task and/or process of learning.